2018
DOI: 10.1177/0895904818773901
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Impact of North Carolina’s Early Care and Education Initiatives on Student Outcomes in Elementary School

Abstract: Based on growing evidence of the long-term benefits of enriched early childhood experiences, we evaluate the potential for addressing gender disparities in elementary school through early care and education programs. Specifically, we explore the community-wide effects of two statewide initiatives in North Carolina on gender differences in academic outcomes in Grades 3 to 5, using administrative student data and information on variation in program availability across counties and over time. We find that althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The current findings indicate that although many faced social stigma and social bias due to their gender roles in the nursing profession [ 6 , 40 ], many overcame the discrimination, social stigma, and social bias due to their strong sense of belonging from their childhood experiences and personal goals. First, many of the participants indicated that their sense of belonging (i.e., being a male nursing professional) was always established and firmed due to their positive early life experiences in their hometown [ 65 ]. Previous studies [ 40 , 43 , 66 , 67 , 68 , 69 ] indicated that individuals often selected their career developments due to their positive early childhood experiences, parental influences, and personal goals.…”
Section: Discussionmentioning
confidence: 99%
“…The current findings indicate that although many faced social stigma and social bias due to their gender roles in the nursing profession [ 6 , 40 ], many overcame the discrimination, social stigma, and social bias due to their strong sense of belonging from their childhood experiences and personal goals. First, many of the participants indicated that their sense of belonging (i.e., being a male nursing professional) was always established and firmed due to their positive early life experiences in their hometown [ 65 ]. Previous studies [ 40 , 43 , 66 , 67 , 68 , 69 ] indicated that individuals often selected their career developments due to their positive early childhood experiences, parental influences, and personal goals.…”
Section: Discussionmentioning
confidence: 99%
“…Gray-Lobe et al (2021) found that effects of the Boston Public Schools pre-k program on college enrollment, SAT-taking, and disciplinary outcomes were larger for boys than for girls. Similarly, previous work on NC Pre-K has also found that effects were largest for boys (Muschkin et al, 2020). In the current study, we test whether male or female students benefit more from NC Pre-K availability.…”
Section: Sexmentioning
confidence: 62%
“…Boys seem to benefit more from formal childcare "in general", with more positive impacts in favour of boys emerging when formal care is introduced after age 3, and especially for boys coming from disadvantaged families (see Datta Gupta and Simonsen 2010; Muschkin et al 2018), even though this second aspect is even less investigated. Studies that take into account simultaneously gender and SES differences are indeed a minority.…”
Section: Discussion and Interpretationmentioning
confidence: 99%